Digital promotion and branding of 'jukolat': A training program for jengkol sellers in Astambul District - Diana Pefbrianti; Heryyanoor Heryyanoor; Al Fath Riza Kholdani; Annisa Febriana; Tassia Sekar Brilliant Santiago; Muhammad Nor Arifudin; Siti Della Harizka; Nor Aliza Ramadani (Universitas Muhammadiyah Magelang, 2024)
In the digital era, the utilization of digital promotional media is crucial for increasing sales. However, many micro-entrepreneurs, such as jengkol sellers, have not optimized its use. This community service activity aimed to enhance the knowledge and skills of jengkol sellers in leveraging digital promotional media to boost their sales. The method involved providing training on entrepreneurship management, branding, and digital marketing, with a focus on utilizing social media and the Canva application. The evaluation results indicated a significant increase in participants' knowledge and positive attitudes, at 83% and 85%, respectively. This suggests that the training was effective in improving participants' ability to create attractive and effective promotional content, thus potentially increasing the sales of Jukolat products.